PECULIARITIES OF PERSONAL IDENTITY OF ADOLESCENTS WITH CEREBRAL PALSY (Psychology Travelogs, 2021)
The article is devoted to research of peculiarities of personal identity of adolescents with cerebral palsy. The phenomenon of «personal identity» in psychology is associated with problems of self-expression, self-determination, freedom of choice, the formation of «Self-concept». Formation of a person's identity begins in adolescence: sense of personal individuality, need for self-affirmation and self-acceptance, trustful communication with peers arise. In conditions of dysontogenesis, the adolescent experiences limitations associated with the social circle, the opportunity to take an active part in entertainment activities, extracurricular activities. Personal development in this case is influenced by internal, individual-psychological (nature of physical disorders, crisis phenomena of adolescence, etc.) and external, psychological-pedagogical factors (inner circle).Adolescents with cerebral palsy have a special type of personal development and identity, where inadequate self-esteem, increased suggestibility, dependence on the opinions of others, explosiveness, infantilism, low level of focus and responsibility come to the fore.Based on empirical research, adolescents with cerebral palsy were found to have a predominance of «diffuse identity», dependence on the opinions of others and parents, difficulties with self-description, low levels of self-development and goal-setting, in contrast to adolescents with normative development. The latter is dominated by the criterion of "achieved identity", a low rate of orientation to the opinion of others (which can be explained by the crisis of adolescence), a positive emotionally-colored attitude to their personality.
Keywords: personal identity; adolescent; cerebral palsy